How to characterize stem cells?: contributions from mathematical modeling - Stiehl, Thomas; Marciniak-Czochra, Anna (Current stem cell reports, 2019)
Adult stem cells play a key role in tissue regeneration and cancer. To translate findings from stem cell biology into clinics, we require a quantitative characterization of stem cell dynamics in vivo. This review explores how mathematical models can help to characterize stem cell behavior in health and disease.
Gesehen am 15.04.2020